If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4y = 7 Solving 6x + -4y = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 6x + -4y + 4y = 7 + 4y Combine like terms: -4y + 4y = 0 6x + 0 = 7 + 4y 6x = 7 + 4y Divide each side by '6'. x = 1.166666667 + 0.6666666667y Simplifying x = 1.166666667 + 0.6666666667y
| N/-2=8 | | -4=-10/86+8 | | (7x^3*(2x^2)^2)/(10x^5) | | 3.4x=2.6x+5.6 | | (x/9)=(x/10)-8 | | x/9=x/10-8 | | 100(2+x)=100 | | (x-1)3+64=0 | | f(x)=-2x^2+5x+40 | | 10(z+2)-2(z-2)=3(z-3)+4(z-1) | | 0.4(0.7-4x)=-1.1x | | 459x+1377-23=8x+160 | | R/-6=-4 | | x^6/5-729=0 | | 50=-2(23-y)+4(y-3) | | v^2+15v+56= | | 2(x+1)(x-1)-(2x+3)(x-2)=0 | | 12m=56+12m | | x^3-4x^2-x-10=0 | | 14x^2=16 | | 4(t+1)=6-1 | | (x+7)2=100 | | -64=-8v | | 18-4x+6=x+9 | | S-15=-15 | | 2x-7x+62=3x+38 | | P=2(pi)r+2x | | 7x-7y=49whatisx | | 8x+9x-3x=52+4 | | (3x-2)/5=(2x-1)/4 | | 2x/3+y/5=0 | | c-8=-17 |